2021
DOI: 10.1186/s12954-021-00468-6
|View full text |Cite
|
Sign up to set email alerts
|

The association between cannabis use and outcome in pharmacological treatment for opioid use disorder

Abstract: Background With the ongoing opioid crisis and policy changes regarding legalization of cannabis occurring around the world, it is necessary to consider cannabis use in the context of opioid use disorder (OUD) and its treatment. We aimed to examine (1) past-month cannabis use in patients with OUD, (2) self-reported cannabis-related side effects and craving, and (3) the association between specific characteristics of cannabis use and opioid use during treatment in cannabis users. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…In particular, the noneuphorigenic cannabinoid CBD is viewed as having potential therapeutic use for the treatment of opioid use disorder (OUD); unfortunately, to date, only short pilot studies have been conducted, and therefore the effectiveness of this treatment remains unclear [138]. However, another recent study found that daily cannabis use was associated with lower opioid use during treatment of OUD [139]. These findings are in agreement with another study that found cannabis users show lower symptoms of withdrawal [140].…”
Section: Opioid Use Disordermentioning
confidence: 99%
“…In particular, the noneuphorigenic cannabinoid CBD is viewed as having potential therapeutic use for the treatment of opioid use disorder (OUD); unfortunately, to date, only short pilot studies have been conducted, and therefore the effectiveness of this treatment remains unclear [138]. However, another recent study found that daily cannabis use was associated with lower opioid use during treatment of OUD [139]. These findings are in agreement with another study that found cannabis users show lower symptoms of withdrawal [140].…”
Section: Opioid Use Disordermentioning
confidence: 99%
“…Recent studies exploring the association between cannabis use on opioid misuse are conflicting. 4,5,6 In three recent studies exploring the association between cannabis and opioid use, two observed a positive association and one observed an inverse association. 4,5,6 The inverse association was observed in a clinical population in treatment for OUD in Ontario, Canada.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, several studies have found that medical cannabis patients report pain management as one of the most common reasons for cannabis use [10][11][12] and that cannabis use was associated with lower opioid use among people who use illicit drugs [13,14]. However, there are also ongoing concerns about cannabis use increasing the risk for non-medical opioid use and opioid and cannabis use disorders, especially among adolescents and young adults [15][16][17][18], and that cannabis use may lead to return to opioid use by people with a history of OUD [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%